Gut Feelings: Bacteria and the Brain - Foster, Jane A. (The Dana Foundation, 2013)
The gut-brain axis—an imaginary line between the brain and the gut—is one of the new frontiers of neuroscience. Microbiota in our gut, sometimes referred to as the “second genome” or the “second brain,” may influence our mood in ways that scientists are just now beginning to understand. Unlike with inherited genes, it may be possible to reshape, or even to cultivate, this second genome. As research evolves from mice to people, further understanding of microbiota’s relationship to the human brain could have significant mental health implications.